2020
DOI: 10.1158/1538-7445.am2020-ct034
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT034: Phase I study of WNT974 + spartalizumab in patients (pts) with advanced solid tumors

Abstract: Background: WNT974, a Porcupine inhibitor, has shown evidence of Wnt pathway inhibition in clinical trials. Dysregulated Wnt signaling has been linked to immunotherapy resistance, suggesting WNT974 may act synergistically with checkpoint inhibitors. Spartalizumab is an αPD-1 mAb with demonstrated clinical activity in solid tumors. Methods: In this Phase I, open-label trial (NCT01351103) adult pts received WNT974 ± spartalizumab; here we report on the dose escalation of the combination. Eligible pts had melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This multi-site trial is still in the recruiting phase for most of the sites participating in the trial but is currently active and set to be completed in 2022. The results of the interim analysis recently demonstrated that a combined use of LGK974 (named as WNT974 in this trial) G spartalizumab alongside effective skin AXIN2 suppression was well tolerated in patients with several types of advanced solid tumors (Janku et al, 2020). Nevertheless, more attention to the end results of this trial would be needed for an overall assessment of the safety and potential of LGK974 for further clinical development.…”
Section: Discussionmentioning
confidence: 94%
“…This multi-site trial is still in the recruiting phase for most of the sites participating in the trial but is currently active and set to be completed in 2022. The results of the interim analysis recently demonstrated that a combined use of LGK974 (named as WNT974 in this trial) G spartalizumab alongside effective skin AXIN2 suppression was well tolerated in patients with several types of advanced solid tumors (Janku et al, 2020). Nevertheless, more attention to the end results of this trial would be needed for an overall assessment of the safety and potential of LGK974 for further clinical development.…”
Section: Discussionmentioning
confidence: 94%
“…Bone-related AEs, including bone fracture, emerged in the initial part of both phase I studies and were not observed subsequently after monitoring protocols, intermittent dosing, and prophylactic bone protective agents were initiated ( Davis et al, 2020 ; Moore et al, 2019 ). This safety profile has been manageable and lacks immune-related AEs, an encouraging attribute for combining these agents with ICI therapy ( Janku et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that depletion of RNF43 enhanced tumor growth in GI cancers and conferred resistance to DNA-damageinducing chemotherapies and γ-radiation in gastric cancer cells (Neumeyer et al, 2019(Neumeyer et al, , 2020. Additionally, preclinical cancer models have shown the responsiveness of RNF43 mutations to Wnt inhibitors, several of which are in clinical trials (Janku et al, 2015(Janku et al, , 2020Yu et al, 2020). Therefore, screening for RNF43 mutational status could direct therapy selections for GI cancer treatments.…”
Section: Discussionmentioning
confidence: 99%